A defensoria pública de Presidente Prudente/SP como espaço sócio-ocupacional do serviço social - Carlos, Maria Carolina Carvalho de (2012)
This research, "The Public Defender of Presidente Prudente / SP as the sociooccupational social work", aimed to reveal the social reality of the social worker acting in the Public Defender of Presidente Prudente, based on approximations of the concrete day-to-day work as well as present the identity of the profession inoccupational social space, besides enabling the construction of questions and concerns so that they may contribute to improving the quality of care, considering its importance in the protection, achievement and accomplishment of social rights. To support the analysis was performed on bibliographical research and field, having as theorical Social Services, the area socio-legal and justice.Starting from a historical reflection on social rights, presented the Public Defender as an important institution in the legal and social areas, focusing on the Regional Presidente Prudente / SP. We also carried out a carefully field research with social workers working in this field, by analyzing the critical points that stood out in interviews. The survey was complemented with the Regional Database, from whichwere evidenced by the prevailing demands and reflect the failure of social policies in their respective areas, the main ones being social care and health. And finally proposals are made for intervention by Social Services in the sociooccupational, and the ethical-political project as a reference horizon and the humanization of care in the areas of socio-legal field